Midnight for Charlie Bone: children of the Red King book 1 (Children of the Red King, 1, 1, 2006)
Charlie Bone's life with his widowed mother and two grandmothers undergoes a dramatic change when he discovers that he can hear people in photographs talking.
BW2714LALA

Charlie Bone and the Time Twister (Children of the Red King, 2, 1, 2003)
Back at Bloor's Academy after Christmas vacation, Charlie finds himself confronted with a new problem when young Henry Yewbeam, who vanished during a game of marbles in 1916, suddenly appears and needs help to find his family.

Charlie Bone and the invisible boy (Children of the Red King, 3, 1, 2004)
Charlie and his friends unite to rescue Ollie, a boy who was turned invisible and made to live in the attics at Bloor's Academy more than a year ago, but they are hindered by a mysterious new student who lives with Charlie's aunts.
Achievement , Rain woman , "I'm going to be a singer" , Hitsville USA , "Get yourself a hit record" , Movin' on up , "Say it loud" , Doing it herself , One step at a time , Appendix: Selected discography , Chronology , Further reading , Index.

Charlie Bone and the castle of mirrors (Children of the Red King, 4, 1, 2005)
Charlie and his magically gifted friends and relatives work together to rescue Billy Raven, a young orphan, from a mysterious and dangerous couple who have adopted him.

Charlie Bone and the Hidden King (Children of the Red King, 5, 1, 2006)
Charlie faces his most dangerous adventure yet when the shadow from the Red King's portrait escapes. Strange things start to happen at Bloor's Academy. A mysterious force, however, is helping Charlie get closer to the truth about his father.

Charlie Bone and the Beast (Children of the Red King, 6, 1, 2007)
When Asa Pike, a Bloor's Academy student with the ability to change into a beast at dusk, goes missing, twelve-year-old Charlie Bone suspects a new classmate, the magically gifted Dagobert Endless, of foul play.